Предмет: Алгебра, автор: Igor171717

Решите производные..

Приложения:

Ответы

Автор ответа: NNNLLL54
0
1); ; y= sqrt[3]{2x-1}cdot (2x-3)^3; ,; ; ; ; y=(2x-1)^{frac{1}{3}}cdot (2x-3)^3\\y'=frac{1}{3} cdot (2x-1)^{-frac{2}{3}}cdot 2cdot (2x-3)^3+(2x-1)^{ frac{1}{3} }cdot 3cdot (2x-3)^2cdot 2=\\= frac{2}{3cdot sqrt[3]{(2x-1)^2}}cdot (2x-3)^3+6cdot sqrt[3]{2x-1}cdot (2x-3)^2\\2); ; y= sqrt[4]{3x+2}cdot (3x-1)^4; ,; ; ; ; y=(3x+2)^{frac{1}{4}}cdot (3x-1)^4\\y'= frac{1}{4}cdot (3x+2)^{-frac{3}{4}}cdot 3cdot (3x-1)^4+(3x+2)^{ frac{3}{4}}cdot 4cdot (3x-1)^3cdot 3=

= frac{3}{4cdot sqrt[4]{(3x+2)^3}}cdot (3x-1)^4+12cdot sqrt[4]{3x+2}cdot (3x-1)^3
Похожие вопросы
Предмет: Алгебра, автор: Dimaluk55104